2007
DOI: 10.1529/biophysj.106.103754
|View full text |Cite
|
Sign up to set email alerts
|

A Mechanical Spike Accompanies the Action Potential in Mammalian Nerve Terminals

Abstract: Large and rapid changes in light scattering accompany secretion from nerve terminals of the mammalian neurohypophysis (posterior pituitary). In the mouse, these intrinsic optical signals are intimately related to the arrival of the action potential E-wave and the release of arginine vasopressin and oxytocin (S-wave). Here we have used a high bandwidth atomic force microscope to demonstrate that these light-scattering signals are associated with changes in terminal volume that are detected as nanometer-scale mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
131
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(136 citation statements)
references
References 41 publications
5
131
0
Order By: Relevance
“…Our results are consistent with data by Kim et al (6) on synapse bundles, where the mechanical changes were also found to be proportional to the voltage change. Optical recordings of dimensional changes in nerves also indicate that displacements are proportional to voltage (6,27). This difference in functional form is important because Iwasa's & Tasaki's data are not consistent with the concept of electrostriction, while the data presented here are actually in good agreement with this concept (see Appendix A for details).…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Our results are consistent with data by Kim et al (6) on synapse bundles, where the mechanical changes were also found to be proportional to the voltage change. Optical recordings of dimensional changes in nerves also indicate that displacements are proportional to voltage (6,27). This difference in functional form is important because Iwasa's & Tasaki's data are not consistent with the concept of electrostriction, while the data presented here are actually in good agreement with this concept (see Appendix A for details).…”
Section: Discussionmentioning
confidence: 57%
“…It is to be expected that the state of the nerve cell depends not only on electrochemical potentials and the conjugated flux of ions but also on all other thermodynamic forces including variations in lateral pressure (resulting in changes of membrane area and thickness) and temperature (resulting in heat flux). It is therefore not surprising that, during the action potential, one finds changes not only in voltage but also in thickness (3)(4)(5)(6), length (5, 7) as well changes in membrane temperature (8)(9)(10)(11). The change of thickness of a single squid axon was found to be on the order of 1 nm, and temperature changes range between 1-100 µK depending on the specimen.…”
Section: Introductionmentioning
confidence: 99%
“…VRAC-mediated neurotransmitter release may be more prominent with astrocytes than with neurons because they are more prone to swell, at least under hypoxic conditions (Mongin, 2015). On the other hand, axons swell slightly upon action potential firing (Fields and Ni, 2010;Iwasa et al, 1980;Kim et al, 2007) and may release ATP through swelling-activated anion channels (Fields and Ni, 2010). A role of VRACs in neurotransmitter release from neurons, however, remains speculative.…”
Section: Vracs In the Release Of Neurotransmittersmentioning
confidence: 99%
“…The shape of the solitary pulses in lipid monolayers and action potentials in cell membranes can be directly compared because fluorescence reports membrane potential in both cases [6,35,36]. There are several striking similarities between our results on lipid monolayers and the data on nerve pulses: (i) both systems support 'all-or-none' pulses which propagate as solitary waves and exist only in a narrow window bound by certain nonlinearities in their respective state diagrams [28,37,38], (ii) the pulses in both systems represent an adiabatic phenomenon [39,40] and are not only electrical but are also inseparably mechanical (deflection and volume), optical (polarization, chirality, fluorescence, turbidity) and thermal (temperature, enthalpy) pulses [5,6,36,37,39,[41][42][43][44][45][46].…”
Section: Biological Implicationsmentioning
confidence: 99%